Kewajiban Perekrutan Tenaga Kerja Lokal dalam Sistem Hukum Ketenagakerjaan di Indonesia - Dian Asmarani (CV Rewang Rencang, 2025)
The obligation to recruit local workers in Indonesia faces challenges due to the absence of binding and strict sanctions and low employer compliance. This study aims to analyze how sanctions can be applied in the obligation to recruit local workers in Surabaya. The analysis is conducted from normative, philosophical, and sociological perspectives, comparing practices in Brazil, India, and Vietnam as references for sanction implementation. Philosophical analysis draws on Rawls’ distributive justice, communitarianism, and utilitarianism. Findings show strong constitutional legitimacy but weak enforcement; proportional sanctions and improved local workforce quality are needed for effective policy implementation.